Understanding integrity practices of the manufacturers in halal food supply chain - Supian, Kamisah; Abd Rahman, Azmawani (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
In the last decade, the demand for halal food has increased significantly. The growth of the halal food demand is expected to provide an opportunity to produce more of halal products, especially food, which is very crucial for a Muslim in ensuring its authenticity. Recently, halal authenticity has been a major concern in the food industry. The issues of adulteration of haram or mushbooh ingredients in food productions (i.e. non-compliance to health or safety standards), non-compliance with Shariah law and contamination with non-halal ingredients need serious attention by all parties involved. This includes food safety, healthy, nutrition and quality. This paper attempts to understand the halal food integrity practices and its challenges along the halal supply chain. The challenges of halal food integrity practices are how to preserve the integrity of halal food along its supply chain that complies with the general principles of Shariah law and zero contamination with non-halal materials/ingredients. Generally, integrity refers to the consistency which synonymous with goodness, such as to do the right thing and to do things right. Halal integrity is to assure the products are being sourced, produced, processed, stored and disseminated parallel with the Islamic values of high quality and safety. To uphold the integrity of halal food is a very challenging task as contamination with non-halal ingredient at one point will disturb the whole halal chain. Thus, the adherence to halal integrity practices is important to be preserved and sustained through the activities of compliance to the law and standards, control, coordination, cooperation, communication and commitment along the supply chain by the manufacturers. As Malaysia to be a world halal hub, preserving and sustaining the integrity of halal food is an obligatory perspective in order to obtain the trust of the consumers. Therefore, the integrity of halal food should be monitored to sustain the authenticity of halal food.